2021
DOI: 10.1016/j.molstruc.2021.130366
|View full text |Cite
|
Sign up to set email alerts
|

Unmasking of crucial structural fragments for coronavirus protease inhibitors and its implications in COVID-19 drug discovery

Abstract: Fragment based drug discovery (FBDD) by the aid of different modelling techniques have been emerged as a key drug discovery tool in the area of pharmaceutical science and technology. The merits of employing these methods, in place of other conventional molecular modelling techniques, endorsed clear detection of the possible structural fragments present in diverse set of investigated compounds and can create alternate possibilities of lead optimization in drug discovery. In this work, two fragment identificatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 52 publications
(54 reference statements)
0
3
0
Order By: Relevance
“…Our group has already performed several extensive studies on the previous SARS-CoV inhibitors [ 3 , [18] , [19] , [24] , [25] , [26] , [27] , [28] , [29] , [30] ]. In this study, we have reported the structural analysis of 69 diverse SARS-CoV-2 3CL pro inhibitors by the regression-based quantitative structure-activity relationship (QSAR) methodologies to identify the fundamental structural features having crucial effects on SARS-CoV-2 3CL pro inhibition.…”
Section: Introductionmentioning
confidence: 99%
“…Our group has already performed several extensive studies on the previous SARS-CoV inhibitors [ 3 , [18] , [19] , [24] , [25] , [26] , [27] , [28] , [29] , [30] ]. In this study, we have reported the structural analysis of 69 diverse SARS-CoV-2 3CL pro inhibitors by the regression-based quantitative structure-activity relationship (QSAR) methodologies to identify the fundamental structural features having crucial effects on SARS-CoV-2 3CL pro inhibition.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 In fact, this tool combined with machine learning has a range of applications in many areas of science such as pharmacology, [5][6][7][8][9][10] genetics and biochemistry, [11][12][13][14][15] and drug discovery for COVID-19. 16 However, the model explainability in machine learning is a highly essential issue [17][18][19][20][21] because machine learning models are mostly considered as black boxes, 17,[21][22][23][24] indicating an ambitious challenge to the progress of machine learning.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, designed drugs for COVID-19 treatment can be classified into four groups including drugs that prevent the replication and synthesis of RNA by targeting critical enzymes for the replication of the virus, drugs that block the binding of spike protein to ACE2 receptor on human cells, drugs that inhibit coronavirus virulence factors and drugs that inhibit a receptor or enzymes in human cells [ 24 ]. 3C-like cysteine protease (3CL pro ) is the main protease of SARS-CoV-2 that catalyzes the cleavage of polypeptides to their effector forms and has essential enzymatic role for virus life cycle [ 25 , 26 ]. So it can be considered as a target for design drugs in COVID-19 treatment [ 27 29 ].…”
Section: Introductionmentioning
confidence: 99%